Principles and tools of research of regionally isolated electrotechnical complex from the standpoint of system analysis - O. V. Arkhipova (Омский научный вестник)
The article discusses the application of system analysis in research of regionally isolated electrotechnical complexes (RIEC) and electrical generation systems with common signs. For such aggregates from the standpoint of system analysis, the concept of a regionally isolated electrical complex is introduced. It is proved that the analyzed electrotechnical complex is a complicated technical system. In relation to a regionally isolated electrotechnical complex a meaningful interpretation of the following principles of the theory of system analysis is given: emergence, optimality and equifinality. Based on a system approach, an integral indicator of the average net present cost of electricity generation is proposed (levelized cost of electricity in the region — LCOER). This indicator is directly applicable to the object considered in the article. On basis of the LCOER indicator, a methodology for the optimal design and operation of a regionally isolated electrotechnical complex is proposed. Its application reduces the total costs of a regionally isolated electrotechnical complex throughout the entire life cycle by 5–15 %, while maintaining the given volumes, quality and reliability of electric energy production.